Nanoindentation creep of tin and aluminium : a comparative study between constant load and constant strain rate methods - Shen, Lu (2013)
Creep properties of polycrystalline Tin (Sn) and single crystal Aluminium (Al) were studied by two nanoindentation methods, i.e., constant load (CL) test and constant strain rate (CSR) test. The indentation strain rate and stress were calculated as the analogies drawn from uniaxial creep analysis. The stress exponent was expressed as the slope of the strain rate–stress curves plotted in the double logarithm scale. Between the two testing methods, the CSR test was clearly shown to be able to detect the creep of Sn in the power-law region, where the grain size had little effect on the creep rate. However, it was found that steady-state creep could not be achieved in the CL test. This has imposed ambiguities in applying the creep analysis developed from conventional creep scheme. The creep displacement from CL test was found unrepeatable for multiple measurements. CL test also has a smaller accessible stress range than that from a CSR test. The gradual variation of the stress exponents, especially for the small grain Sn sample, during holding process in the CL test could be due to the participation of the other rate controlling mechanisms which were closely related to the non-steady-state creep behaviour.